Protective effects of black garlic extract on sperm quality and liver histopathology following cigarette smoke exposure: an in vivo experimental study - Lisdiana; Amida, Nurul; Susanti , Dwi; Lamondo, Djuna; Basar, Annisa (Universitas Muhammadiyah Purwokerto, 2026)
Background: Cigarette smoke contains numerous toxic compounds that generate reactive oxygen species, leading to oxidative stress that can impair reproductive function and induce liver damage. Natural antioxidants such as black garlic have been reported to possess strong free radical–scavenging properties. Purpose: This study aimed to evaluate the protective effects of black garlic extract on sperm quality, liver enzyme levels, and liver histopathology in rats exposed to cigarette smoke. Methods: A randomized post-test-only control group experimental design was used. Twenty-five male Wistar rats were divided into five groups: normal control, cigarette smoke exposure, and three treatment groups receiving black garlic extract at doses of 250, 500, and 1000 mg/kg body weight for 30 days. Sperm concentration, viability, and motility were assessed. Liver function was evaluated using serum ALT and AST levels, and liver histopathology was examined using hematoxylin–eosin staining. Data were analyzed using one-way ANOVA followed by post hoc tests. Results: Cigarette smoke exposure significantly reduced sperm concentration, viability, and motility and induced hepatocellular degeneration and necrosis. Administration of black garlic extract improved sperm parameters and reduced histopathological liver damage, with the most pronounced protective effect observed at a dose of 500 mg/kg body weight. However, no significant differences were observed in serum ALT and AST levels among groups. Conclusion: Black garlic extract exerts protective effects against cigarette smoke–induced reproductive and hepatic damage, with the most effective dose observed at 500 mg/kg body weight. These findings support its potential as a natural antioxidant for mitigating oxidative damage. Further studies are required to elucidate the underlying molecular mechanisms and identify the active compounds responsible for these effects.